Pengaruh penggunan fermentasi tepung kulit buah kakao ( Theobroma cacao L.) dalam pakan terhadap efisiensi pemanfaatan pakan dan pertumbuhan ikan mas ( Cyprinus carpio.) - Seravina Seravina; Subandiyono Subandiyono; Agung Sudaryono (Departemen Akuakultur FPIK UNDIP, 2019)
Cacao pod husk (Theobroma cacao L.) is waste or by-products of agro-industry that was produced from cacao plants. The nutritional content of cacao pod husk consisted of 9,15% protein, 1,96 % lipid, 25,64 % crude fiber, 10,39% ash, and 52,86% nitrogen-free extract (NFE). Crude fiber from cacao pod husk was difficult to be digested by fish. The solution for that constraint was by applying fermentation proccess. This experiment was aimed to observe the influence of cacao pod husk flour which has been fermented first before added into the practical diets, on the feed efficiency and growth of carp (Cyprinus carpio). The trial fish used were carp (C. carpio) with an initial average body weight of 6,54 ± 0,07 g/fish. Feeding frequency applied was twice a day, i.e. at 08.00 a.m and 16.00 p.m. and by appliying an at satiation method. The fishes were cultured for 42 days with the stocking density of 1 fish/ 2L. The experimental method used was completely randomize design (RCD) with 4 treatments and 3 replicates. The treatment of A, B, C, and D were the trial diets with the concentration of cacao pod husk flour of 0, 10, 20, and 30%, respectively. The data measured were feed consumption, feed efficiency (FE), protein efficiency ratio (PER), growth (G), spesific growth rate (SGR), and survival rate (SR). The data showed that the use of fermented cacao pod husk flour in the diets resulted significant by effects (P<0,05) on the feed consumption, FE, PER,G, SGR, and SR. Treatment C resulted on the values of feed consumption i.e. 190.1±2.98g, FE i.e. 88.19±8.09%, PER i.e. 2.66±0.24%, G i.e. 7,26±0,11, SGR i.e. 1.68±0.13%, and SR i.e. 96,00±4,00%. The water quality parameters during this observe were varied between suitable range for fish life. It was concluded that the diet containing 20% of fermented cacao pod husk flour resulted on better feed efficency and growth of the carp.